1998
DOI: 10.1523/jneurosci.18-16-06138.1998
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C and A3Adenosine Receptor Activation Inhibit Presynaptic Metabotropic Glutamate Receptor (mGluR) Function and Uncouple mGluRs from GTP-Binding Proteins

Abstract: One of the most prominent roles of metabotropic glutamate receptors (mGluRs) in the CNS is to serve as presynaptic receptors that inhibit transmission at glutamatergic synapses. Previous reports suggest that the presynaptic effect of group II mGluRs at corticostriatal synapses can be inhibited by activators of protein kinase C (PKC). We now report that activation of PKC inhibits the ability of group II and group III mGluRs to regulate transmission at three major synapses in the hippocampal formation. Thus, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
109
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(125 citation statements)
references
References 50 publications
15
109
0
1
Order By: Relevance
“…The PKC family of Ser/Thr kinases (Nishizuka 1995) regulates neuronal activity at different levels, including neurotransmitter release, neurotransmitter receptor function, and gene expression (Ben-Ari et al 1992;Meberg et al 1993;Macek et al 1998;Manseau et al 1998;Kleschevnikov and Routtenberg 2001). There are at least 10 genes coding for PKC family members.…”
Section: Discussionmentioning
confidence: 99%
“…The PKC family of Ser/Thr kinases (Nishizuka 1995) regulates neuronal activity at different levels, including neurotransmitter release, neurotransmitter receptor function, and gene expression (Ben-Ari et al 1992;Meberg et al 1993;Macek et al 1998;Manseau et al 1998;Kleschevnikov and Routtenberg 2001). There are at least 10 genes coding for PKC family members.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in the present work we found that CXCL16 exerts neuroprotection against Glu insult only in the presence of functional A 3 R, the inactivation of all of the other ARs being unable to limit the CXCL16 effect. In rodents, among ARs, A 3 R has the lower affinity for ADO and is expressed at low levels in the brain (Ji et al, 1994), including the hippocampus (Dunwiddie et al, 1997;Macek et al, 1998) and the cerebral cortex (Brand et al, 2001). The ability of A 3 R to contribute to neuroprotection is controversial: in vivo studies suggest that differences in timing of intraperitoneal A 3 R agonist administration may alter the outcome of ischemic brain injury (Von Lubitz et al, 1995, 2001.…”
Section: Discussionmentioning
confidence: 99%
“…NMDA receptors are essential to AD initiation and propagation [26]. Block of A 3 receptors, in removing A 3 receptor-mediated impairment of the feedback inhibition of glutamate release exerted by specific metabotropic glutamate receptor subtypes [42], may reduce the participation of glutamate in triggering the AD.…”
Section: Discussionmentioning
confidence: 99%